Management of Tahfidz Quran Programs in Shaping Elementary Students' Character - Sulastri, Sri; Wiyani, Novan Ardy; Anam, Rif’at Shafwatul (el-Tarbawi, 2024)
The current study intends to analyze the management of the Tahfidz program in shaping students' character. The non-mulazamah program became the subject of the study. A qualitative approach using a case study method was employed in this study. Data collection techniques included interviews, observation, and documentation. Data were generated from the analysis process, comprising data reduction, data display, and conclusion drawing. The results showed that the management of the Tahfidz program was successful in shaping students’ characters based on four indicators. First, in the planning stage, the madrasah conducted a need analysis and prepared stakeholders to ensure proficiency in reading the Qur'an, creating an ideal learning environment. Second, in organizing the Tahfidz program, the madrasah had a clear purpose, well-defined job responsibilities, and adequate facilities to support the program. Third, the Madrasah leaders implemented a situational leadership style during the program's execution. Finally, in the control phase, the management team ensured that the program produced quality outcomes, with many students surpassing the expected targets. The study indicates that the Tahfidz program nurtures students’ characteristics such as discipline, responsibility, independence, and compliance.